2023
DOI: 10.1098/rsos.221008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental addition of marine-derived nutrients affects wildflower traits in a coastal meta-ecosystem

Abstract: Organismal movement can bring individuals, resources and novel interactions across ecosystem boundaries and into recipient habitats, thereby forming meta-ecosystems. For example, Pacific salmon ecosystems receive large marine-derived nitrogen subsidies during annual spawning events, which can have a wide range of effects on aquatic and terrestrial plant species and communities. In this study, we evaluate the effects of cross-ecosystem nutrient subsidies on terrestrial plant growth and reproduction. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Some prior work in our study region has shown a positive relationship between salmon density and percent nitrogen only in nitrogen indicator species such as salmonberry and false lily‐of‐the‐valley (Hocking & Reynolds, 2011), and other research showed relationships between salmon and percent nitrogen in false azalea and salmonberry using comparisons above and below waterfalls on a limited number of salmon‐bearing rivers (Mathewson & Reimchen, 2003). Conversely, experimental evidence found no relationship between salmon carcass deposition and foliar percent nitrogen in estuarine meadow plants (Dennert et al., 2023). Plant elemental composition can vary due to competition, subsidies, and nutrient limitation (Sterner & Elser, 2002), and we may only observe changes in elemental composition during excess nutrient deposition, resulting in luxury (or excess) consumption of this nutrient (Ågren, 2008; Chapin, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some prior work in our study region has shown a positive relationship between salmon density and percent nitrogen only in nitrogen indicator species such as salmonberry and false lily‐of‐the‐valley (Hocking & Reynolds, 2011), and other research showed relationships between salmon and percent nitrogen in false azalea and salmonberry using comparisons above and below waterfalls on a limited number of salmon‐bearing rivers (Mathewson & Reimchen, 2003). Conversely, experimental evidence found no relationship between salmon carcass deposition and foliar percent nitrogen in estuarine meadow plants (Dennert et al., 2023). Plant elemental composition can vary due to competition, subsidies, and nutrient limitation (Sterner & Elser, 2002), and we may only observe changes in elemental composition during excess nutrient deposition, resulting in luxury (or excess) consumption of this nutrient (Ågren, 2008; Chapin, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leaf tissues are more likely to respond to changes in nutrient availability than other above-or belowground tissues (Chapin, 1980;Marschner, 1995). Prior work in the region has also found a relationship between salmon carcass deposition and flowering plant leaf size (Dennert et al, 2023), and work across the Pacific northwest has found a relationship between salmon, tree growth, and forest productivity (Brown et al, 2020;Kieran et al, 2021;Quinn et al, 2018;Reimchen & Arbellay, 2019;Reimchen & Fox, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nutrients permeate stream environments, increasing aquatic nutrient loads (Levi et al, 2013); biofilm and plankton biomass (Collins et al, 2015); and change fish abundance, individual fish biomass, behavior, and spawning success (Swain and Reynolds, 2015;Collins et al, 2016). Salmon presence also affects nearby terrestrial sites by changing plant communities and increasing the abundance of nitrophyllic plant species (Mathewson et al, 2003;Hocking and Reynolds, 2011); increasing plant growth, fruit growth, and other plant traits (Sayer, 2008;Quinn et al, 2018;Siemens et al, 2020;Dennert et al, 2023); and increasing bird diversity and abundance (Christie and Reimchen, 2008;Wagner and Reynolds, 2019). In addition, their carcasses provide food for numerous large mammals such as bears and wolves (Hocking et al, 2009;Reimchen, 2017), small mammals such as mink and river otter (Dolloff, 1993;Ben-David et al, 1997), and insects (Hocking and Reimchen, 2006;Hocking et al, 2009;Reimchen, 2017;Rammell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%